Moderation of Madhhabs in West Sumatra Towards Hadhanah of Minors Whose Mothers Remarry - Sulfinadia, Hamda; Roszi, Jurna Petri (El-Usrah: Jurnal Hukum Keluarga, 2024)
This study examines the implementation of the fiqh madhhab of West Sumatran society regarding the hadhanah rights of minors whose mothers remarry. The study aimed to map the moderation of the West Sumatran madhhab of society, known as the Shafi'i madhhab. This research uses qualitative methods with a sociological approach to law. Seventeen cases were found in 3 research locations: Pariaman, Luhak Agam, and Luhak Fifty Cities. The location was chosen because it is an area with a higher level of moderation than other regions in West Sumatra. The location of this study was determined using a purposive random sample technique. In the people of West Sumatra, the right of hadhanah remains with the mother, even if the mother remarries. This opinion is in harmony with that of the Maliki Madhhab. The matrilineal kinship system in Minangkabau also supports this: the child belongs to the mother and her family. When the mother's father is divorced, the child follows his mother. However, in 3 cases, it was found that the father took away the rights of a minor whose mother remarried. Basically, the people of West Sumatra have practiced the moderation of mazhab. This is evident from their practice, where they indirectly practice the diversity of mazhab opinions in the case of hadhanah of minors whose mothers remarry.